Extraction, Identification, and Health Benefits of Anthocyanins in Blackcurrants (Ribes nigrum L.) - Lei Cao; Yena Park; Sanggil Lee; Dae-Ok Kim (Applied Sciences, 2021)
The fruit of the blackcurrant (Ribes nigrum L.) is round-shaped, dark purple, bittersweet, and seed-containing edible berries. The blackcurrant has been used as a traditional medicine in both Asia and European countries. It is known as a rich source of antioxidants, largely due to its high content of phenolic compounds, especially anthocyanins. Studies on anthocyanins from blackcurrants have adopted different extraction methods and a panel of anthocyanins has been identified in them. Research on the health benefits of blackcurrant anthocyanins has also grown. To present a general overview of research in blackcurrant anthocyanins, this review focuses on the extraction methods of anthocyanins from blackcurrants and the molecular mechanisms underlying their health benefits.